LOCAL LANGUAGES IN INDONESIA: LANGUAGE MAINTENANCE OR LANGUAGE SHIFT? - Abigail C. Cohn; Maya Ravindranath (Linguistik Indonesia, 2014)
The choice and subsequent development of Bahasa Indonesia as the national language following the founding of the Republic of Indonesia in 1945 is widely cited as a great success story in language planning. With the increased use of Indonesian—both formal (bahasa resmi) and informal (bahasa sehari-hari)—in all facets of daily life, the question arises as to whether Indonesia will continue as a highly multilingual society or move toward monolingualism. We consider this issue from the perspectives of research on language policy, language endangerment, and language ideologies. As a case study, we consider current trends and shifts in the use of Javanese by younger speakers as influenced by the increased use of Indonesian. As Indonesian takes over in more and more domains of communication and intergenerational transmission of Javanese breaks down, we are led to conclude that even a language with over 80 million speakers can be at risk, a trend that has serious implications for all of the local languages of Indonesia.